Implementasi Manajemen Mutu Berbasis Sekolah untuk Meningkatkan Mutu Pendidikan di SD Lamper Kidul 01 Kota Semarang (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Improving the quality of education is one of the main challenges in the management of education in Indonesia. One approach that is considered effective to achieve the quality of education is School-Based Management (MMBS), which gives schools greater authority to manage resources and decision-making independently. This article discusses the implementation of School-Based Quality Management (MMBS) at SD Lamper Kidul 01 Semarang City, as well as the challenges faced in its implementation. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and document analysis. The results of the study show that the implementation of MMMBS at SD Lamper Kidul 01 Semarang City has shown several successes. The success of improving the quality of SD Lamper Kidul 01 through the implementation of School-Based Quality Management (MMBS) can be concluded: (1) The foundation of quality management has been formed, but its implementation still needs to be strengthened, especially in the aspects of data-based evaluation, continuous improvement, and learning innovation, (2) The key to improvement lies in the leadership of the principal, teacher empowerment, and the active and meaningful involvement of all school residents, (3) Understanding of MMBS has begun to form, especially among school principals and teachers, (4) The implementation of MMBS has not been maximized, because it is still administrative and has not touched a sustainable quality culture, (5) The involvement of external stakeholders (committees & parents) is still not optimal and needs to be improved through socialization and real involvement, (6) It is necessary to increase the capacity of human resources in quality management, and strengthening the reflection-based evaluation system.